(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The article examines the issues of early prevention of juvenile delinquency, the reasons and motives for their commission. Also, modern programs for the prevention of juvenile delinquency are emphasized. The authors highlighted the process of development of methods for determining preventive measures. Particular attention is paid to setting objectives to achieve the goals, highlights the issues of determining the factors of prevention of delinquency among minors.